PENYULUHAN EVALUASI STATUS KESUBURAN TANAH UNTUK MENUNJANG PENINGKATAN PRODUKTIVITAS PADI (STUDI KASUS DESA TIRTAYASA SERANG BANTEN) - Firnia, Dewi; Tresna S, Ari; Setiawan, Johan (Universitas Sultan Ageng Tirtayasa, 2022)
Tirtayasa Village, Serang City, Banten is a large enough rice-producing area to meet theneeds of the community. In managing their agricultural land, farmers use various kinds ofchemicalssuchasinorganicfertilizersandpesticidestoincreasetheiragriculturalyields.Excessive use of inorganic fertilizers and pesticides that are not in accordance with the dosage willcause contamination of the paddy field soil which has a negative impact on the chemical andbiological properties of paddy soil which generally affects the quality of paddy soil. Soil chemicalproperties are an indicator to determine the level of nutrient status in soil. The purpose ofconducting counseling on evaluating the status of soil fertility in paddy fields in Tirtayasa Village isto examine whether soil fertility factors are one of the factors causing the decline in riceproductivity levels in Tirtayasa Village. increasing rice productivity. The results of the activities ofseveral farmers stated that their paddy fields had hard physical conditions, hard soil was difficult tocultivate during the dry season, cracked soil conditions, and rice plants were susceptible to pests, atthe time of seeding the success rate of seeds sown was small, only about 45% could grow and yieldswere low. low yield per planting. Based on the results of the evaluation of the nutrient status of thepaddy fields in Tirtayasa Village, it showed that the status of the soil N element was moderate; Pmedium soil; K medium soil and neutral soil pH (6-7). So it can be recommended that fertilizationgiven for the next rice planting season is the use of N fertilizer in the form of urea at a dose of 250-300 Kg/Ha, the use of SP 36 fertilizer at a dose of 50-75 Kg/Ha, the use of 50 Kg/Ha KCl or can bereplaced with the return of straw to the land as much as 5 tons /Ha.